Altered Brain Fraction Amplitude of Low Frequency Fluctuation at Resting State in Patients With Early Left and Right Bell’s Palsy: Do They Have Differences? - Han, Xiaowei; Li, Haimei; Wang, Xiaochun; Zhu, Yijiang; Song, Tianbin; Du, Lei; Sun, Shilong; Guo, Runcai; Liu, Jing; Shi, Sumin; Fu, Chao; Gao, Wenwen; et al. (Frontiers in Neuroscience, 2018)
Purpose: Bell’s palsy refers to acute idiopathic unilateral facial nerve palsy. It is a common disorder of the main motor pathway to the facial muscles. This study aimed to investigate the abnormal fraction amplitude of low frequency fluctuation (fALFF) of the brain in patients with early left and right Bell’s palsy. Materials and Methods: Sixty-seven patients (left 33, right 34) and 37 age- and sex-matched healthy controls underwent resting-state functional magnetic resonance imaging (R-fMRI) examination. The fALFF values were measured from all subjects and were compared among the left palsy, right palsy, and control groups. Then, correlations between the Toronto Facial Grading System (TFGS) scores of the patients and the fALFF values of abnormal brain regions were analyzed. Results: Significant group differences in fALFF values among the three groups were observed mainly in the cerebral cortical, subcortical, and deep gray matter regions. Compared with the right Bell’s palsy group, the left Bell’s palsy group showed significantly decreased fALFF values in the left temporal pole of the superior temporal gyrus (TPOsup), right supramarginal, left and right middle cingulate cortex (MCC), left superior frontal gyrus (SFG), and left precentral gyrus (PreCG), and increased fALFF values were observed in the right SFG and PreCG. Furthermore, altered fALFF values correlated positively with the TFGS scores in the left superior TPO, bilateral MCC, and right PreCG, and correlated negatively with the TFGS scores in the right SFG of the left Bell’s palsy group. Altered fALFF values correlated positively with the TFGS scores in the bilateral MCC and right PreCG and correlated negatively with the TFGS scores in the left superior TPO and SFG of the right Bell’s palsy group. Conclusion: Regulatory mechanisms seem to differ between patients with left and right early Bell’s palsy. The severity of the disease is associated with these functional alterations.